2010
DOI: 10.1016/j.biosystemseng.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ammonia emission potential from concrete slat designs for pig housing

Abstract: In growing-finishing pig houses, ammonia (NH 3) is mainly produced by excreta on the concrete slatted floor surface and in the slurry pit. The objective of this study was to reduce the amount of NH 3 emissions produced on the fouled floor surfaces of growing-finishing pig houses by finding a slat design that minimises the contact between excreta and concrete. Concrete slat prototypes were tested with regards to their NH 3 emission potential under fouling simulations. Three factors were studied; the slats cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Though, a solid floor with a double slope (V-shape) to a central drain (which promotes urine drainage) reduces in 50% (BRAAM et al, 1997), as well as the perforation presence in a solid floor (less than 0.5% of total floor area) reduces 46% NH 3 volatilization (NDEGWA et al, 2008). Recently, HAMELIN et al (2010) noted that in slatted floors, a border insertion on the upper beam surface (along the length) reduces NH 3 emission from 23 to 42%, because it decreases the contact surface area between urine and beam side faces, diverting urine directly to the channel under them. Furthermore, the combination of floor cleaning (scraping and/or washing) and urine drainage to a central drain reduces emission in 65%, when compared to slatted floor (BRAAM et al, 1997, SOMMER et al, 2006.…”
Section: Facility Designmentioning
confidence: 99%
“…Though, a solid floor with a double slope (V-shape) to a central drain (which promotes urine drainage) reduces in 50% (BRAAM et al, 1997), as well as the perforation presence in a solid floor (less than 0.5% of total floor area) reduces 46% NH 3 volatilization (NDEGWA et al, 2008). Recently, HAMELIN et al (2010) noted that in slatted floors, a border insertion on the upper beam surface (along the length) reduces NH 3 emission from 23 to 42%, because it decreases the contact surface area between urine and beam side faces, diverting urine directly to the channel under them. Furthermore, the combination of floor cleaning (scraping and/or washing) and urine drainage to a central drain reduces emission in 65%, when compared to slatted floor (BRAAM et al, 1997, SOMMER et al, 2006.…”
Section: Facility Designmentioning
confidence: 99%
“…Gilhespy et al (2009) examined the role of additional straw in reducing ammonia emission by reducing airflow across surfaces soiled by urine, and by immobilization of ammonium-N. An increase of 100% straw, broadcast over the entire floor, reduced NH3 emission from pigs by only c. 20%. Hamelin et al (2010) showed that design of concrete slat could affect ammonia emission when fouled. Compared with the control design that is typically used in pig houses, the presence of a notch resulted in average reductions between 23 and 42%.…”
Section: 51mentioning
confidence: 99%
“…En los cebaderos porcinos, dicha reacción tiene lugar tanto en la solera emparrillada húmeda como en las fosas de purines situadas debajo de las parrillas. En consecuencia, los niveles de las emisiones de NH 3 varían notablemente en función de las condiciones prevalentes en el alojamiento porcino: velocidad de aire sobre la solera, superficie sólida y emparrillada, temperatura ambiente, pH y/o concentraciones amoniacales totales en el purín (Blanes-Vidal et al, 2008;Hamelin et al, 2010;Philippe et al, 2011).…”
Section: Introductionunclassified